Adrenal disease: a clinical update and overview of imaging. A review - Ctvrtlik, Filip; Koranda, Pavel; Tichy, Tomas (Biomedical papers, 2014)
Aim: The aim of this article is to provide an overview of the most frequent clinically significant adrenal diseases and to describe the latest trends in their diagnostics, particularly by means of imaging techniques.Methods: The authors reviewed standard textbooks and subsequently conducted a search using the PubMed (Public/Publisher MEDLINE) electronic database by the year 2013 with the following search terms: adrenal masses, adrenal adenoma, phaeochromocytoma, adrenocortical carcinoma, metastases, incidentalomas, hypercortisolism, hyperaldosteronism.Results: If adrenal disease is clinically suspected, hormone tests are performed to detect adrenal hyperfunction and imaging studies are used to assess the nature of adrenal lesion. The most frequent syndromes include hypercortisolism, primary hyperaldosteronism, and phaeochromocytoma. The clinically most significant pathologies of the adrenal glands are adenomas and adrenal hyperplasia, adrenocortical carcinomas, phaeochromocytomas, and metastases. Given the availability and improved quality of imaging techniques, adrenal incidentalomas are detected increasingly often. In these cases, it is necessary to rule out hormonal activity and malignancy. Incidentalomas can be associated with clinical syndromes of adrenal hormone overproduction. In most cases, they are clinically silent. In some cases, the definitive diagnosis can be determined as early as during the initial examination with an imaging technique (most frequently, a CT scan). If the finding is inconsistent, other imaging techniques can be used: CT contrast washout analysis, MRI, SPECT or PET/CT.Conclusion: In the case of adrenal gland disorders, correct interpretation of the results of laboratory tests and imaging studies is essential for further management of these patients.
Keywords: adrenal masses; adrenal adenoma; phaeochromocytoma; adrenocortical carcinoma; metastases; incidentalomas; computed tomography; PET/CT